Corporate Governance Country Assessment : Mauritius - World Bank (Washington, DC, 2013)
This report provides an assessment of the corporate governance practices of listed companies in Mauritius within the broader context of the institutional capacity needed to ensure compliance and enforcement. Strengths and weaknesses are highlighted and policy recommendations made where appropriate. Mauritius capital markets are well developed relative to other African economies. There are 40 companies listed on the Official Market of the Stock Exchange of Mauritius, with a total market capitalization of USD 1billion, equivalent to 21.6 percent of GDP for 2000. While overall, the Mauritius economy has done remarkably well over the past 30 years, with a real GDP growth of 5.9 percent a year between 1973 and 1999, this assessment of corporate governance highlights issues that may have contributed to a slowing of growth in recent years.